Precarious Settlements and Socio-environmental Vulnerability: The Case of the Valinhos II Occupation, Passo Fundo, RS - Garbin, Lívia; Tiecher , Francieli (Scientific Journal ANAP, 2025)
Objective – This article aims to analyze basic sanitation conditions in the Valinhos II Occupation, in Passo Fundo/RS, and to present technical-urban proposals developed within the scope of the extension program of Atitus Educação College.Methodology – The research adopted a qualitative approach, based on literature review, technical visits, field surveys, participatory workshops with residents, and the development of proposals.Originality/Relevance – The study contributes to the discussion on urban precariousness and the role of educational institutions and their trained professionals in promoting sustainable solutions for cities and, consequently, for their residents.Results – The main results point to the lack of adequate basic infrastructure and the urgent need for interventions focused on sanitation, drainage, and solid waste management.Theoretical/Methodological Contributions – The study reinforces the importance of interdisciplinarity between Architecture and Engineering in formulating urban proposals in vulnerable contexts.Social and Environmental Contributions – The proposals developed offer viable and low-cost alternatives to improve the living conditions of the local population, promoting social inclusion, public health, and environmental preservation.
Keywords: Urban settlements; Sanitation; University Extension